Sixty Years of Hail Suppression Activities in Mendoza, Argentina: Uncertainties, Gaps in Knowledge and Future Perspectives - Rivera, Juan A.; Otero, Federico; Naranjo Tamayo, Elizabeth; Silva, Martín (Frontiers in Environmental Science, 2020)
This paper provides a perspective based on the evaluation of scientific evidence of hail suppression activities in Mendoza, Argentina. The province of Mendoza was home to several cloud-seeding projects over the years intended to prevent hail damage to agriculture. Those projects were motivated by the paramount importance of wine production for the regional and national economy. We discuss the uncertainties and gaps in knowledge identified in the results from the hail suppression activities, framing the available research over the study area on a global context. The results of this study indicate that there is no unequivocal scientific evidence that proves a statistically significant reduction of hail frequency and size as a consequence of hail suppressing activities in Mendoza. Such lack of evidence questions the reliability of the projects after almost 60 years of cloud seeding. By analyzing the existing gaps in knowledge in terms of observations, modeling evaluations and understanding of severe convective systems, the study provides a description of future directions and alternatives for hail damage mitigation that need a better science-policy integration. This study can be replicated in other regions where hail suppressing activities are taking place.